Platelets and aspirin-induced asthma : pathogenesis and melatonin - Evsyukova, Helen V. (Elsevier/Academic Press, 2014)
Platelets and Aspirin-Induced Asthma is the first book to be published that reflects research conducted on aspirin-induced asthma pathogenesis. It is examined through positions of neuroimmunoendocrine interactions in organism. The Melatonin hormone plays a key role, being the regulator and coordinator of complicated and interrelated biological processes. This new concept of aspirin-induced asthma pathogenesis suggests new methods for treatment of this disease by means of correcting the melatonin content in the patient's organism. Investigations into the mechanisms of aspirin-induced asthma.